Speech Disorder (Stuttering) in Students of Batu Merah SLB, Sirimau District, Ambon City - Tomia, Marisa; Somelok, Grace; Latupeirissa, Elsa (Mirlam: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study seeks to thoroughly investigate the behaviors of a stuttering student at SLB Negeri Batu Merah in Sirimau District, Ambon City. The researcher delineates the study into numerous micro sub-problems: the communication context, communication occurrences, and communication behaviors of stuttering pupils at SLB Negeri Batu Merah, Sirimau District, Ambon City. The research methodology is a qualitative case study technique underpinned by psycholinguistic theory. This study focuses on a single individual, Muhamad Basir, a student with special needs (SLB) who suffers from a speech impairment (stuttering). The research encompasses the design, the researcher's involvement, data sources, the research setting, data collection methods, data analysis techniques, and validity checks through triangulation and literature review. The research findings indicate that the communication circumstances of students who stutter at SLB Negeri Batu Merah, Sirimau District, Ambon City, during class activities are highly tense, and their speech is markedly halting. This contrasts with the scenario outside the classroom at recess, when their pronunciation is less hesitant. The communication event encompasses several elements that the researcher will elucidate, specifically through the term "speaking," which includes the setting, both within and outside the classroom, and the participants, comprising teachers, parents, and Muhamad Basir, a student from SLB Negeri Batu Merah in Sirimau District, Ambon City, who experiences mild stuttering. Muhamad Basir, a student at Batu Merah State Special School in Sirimau District, Ambon City, predominantly employs nonverbal communication above spoken communication during interactions.